1997
DOI: 10.1111/j.1471-0528.1997.tb11980.x
|View full text |Cite
|
Sign up to set email alerts
|

A single cervical fetal fibronectin screening test in; population at low risk for preterm delivery: an improvement on clinical indicators?

Abstract: Objective To assess the accuracy of a single cervical fetal fibronectin test to predict spontaneous preterm Design A prospective blind cohort study.Setting Antenatal clinic of a teaching hospital in a Brussels semiurban area.Participants An unselected group of 170 women followed at the antenatal clinic.Methods A single cervical sample was obtained between 24 and 33 completed weeks of pregnancy. The fibronectin test was compared with clinical evaluation and their predictive properties were assessed.Results Fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 16 publications
1
7
0
2
Order By: Relevance
“…Contradicting observations have been found regarding the role of fFN for predicting preterm births (Faron et al, 1997;Revah et al, 1998;Moore, 1999;Sakai et al, 2003). Our results indicated that fFN had a higher recent predictive value and negative predictive value for predicting preterm birth, but the positive predictive value appeared lower.…”
Section: Relationship Between Ffn and Preterm Birthsupporting
confidence: 49%
“…Contradicting observations have been found regarding the role of fFN for predicting preterm births (Faron et al, 1997;Revah et al, 1998;Moore, 1999;Sakai et al, 2003). Our results indicated that fFN had a higher recent predictive value and negative predictive value for predicting preterm birth, but the positive predictive value appeared lower.…”
Section: Relationship Between Ffn and Preterm Birthsupporting
confidence: 49%
“…There were three studies in asymptomatic women [87][88][89] and five studies in symptomatic women that fulfilled our definition of high-quality test accuracy studies. 85,[90][91][92][93] The methodological quality of the included primary studies is summarised in Figure 8 85 with a summary LR-of 0.50 (95% 0.43-0.59) (χ 2 heterogeneity test p = 0.00) ( Figure 13).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…The presence or absence of fFN detected by the test is one of the best predictors of preterm birth found to date, particularly for the determination of which women presenting with PTL are not at immediate risk for preterm birth . Numerous systematic reviews/meta‐analyses, clinical trials and cohort studies reporting diagnostic test properties of the fFN test in different obstetrical populations have demonstrated high negative predictive values (between 75% and 100%), indicating that women who test negative for fFN have a high probability of not delivering within the subsequent 7–14 days. The utilisation of the fFN test for the evaluation of women presenting with PTL has achieved measurable reductions in hospital admissions, maternal transfer rates and length of stay for PTL in numerous settings; however, to our knowledge, an evaluation at a health system level has not been carried out previously.…”
Section: Introductionmentioning
confidence: 99%